Advanced transport phenomena : fluid mechanics and convective transport processes - Leal, L. Gary (Cambridge series in chemical engineering., 2007)
"Advanced Transport Phenomena is ideal as a graduate textbook. It contains a detailed discussion of modern analytic methods for the solution of fluid mechanics, and heat and mass transfer problems, focusing on approximations based upon scaling and asymptotic methods, beginning with the derivation of basic equations and boundary conditions and concluding with linear stability theory. Also covered are unidirectional flows, lubrication and thin-film theory, creeping flows, boundary layer theory, and convective heat and mass transport at high and low Reynolds numbers. The emphasis is on basic physics, scaling and non-dimensionalization, and approximations that can be used to obtain solutions due either to geometric simplifications, or large or small values of dimensionless parameters. The author emphasizes setting up problems and extracting as much information as possible short of obtaining detailed solutions of differential equations. The book is also focused on the solutions of representative problems. This reflects the author's bias toward learning to think about the solution of transport problems."--Publisher's description